(untitled) (Research, Society and Development, 2022)
Introduction: Tinnitus is a symptom reported by the individual as a sound sensation, perceived in the ears or head, continuously or intermittently without external source of stimulation. This alteration has variable causes and may be associated with patients with hearing loss or normal hearing. Among main methods cited as treatment possibilities, hearing aids has been presented as a widely used resource. Objective: To carry out an integrative literature review on the effectiveness of hearing aids in rehabilitation of patients with tinnitus. Method: A search for articles was carried out in electronic databases: PubMed, Scielo, Scopus, Lilacs, Web of Science, with publication date from 2000 to 2020. Results: The sample consisted of 16 works where all concluded that somehow, in most cases, hearing aids associated or not with other resources used in treatment, contributes to a satisfactory result in improvement or disappearance of the symptom. Seven of sixteen articles related hearing aids to some type of guidance. The combination of these two factors could be considered an excellent combination as it favors the reduction of tinnitus sensation relatively quickly and efficiently. None of the articles analyzed showed an opposite or unsatisfactory result regarding its use.